Strength of Product Quality to Improve Competitiveness - Muchammad Alfan Purnama; Erry Sunarya; Asep Muhamad Ramdan (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
In the background here, the problem is that the dependent variable is competitiveness and the independent variable is product quality. The purpose of this study was to determine the effect of differentiation strategies on the competitiveness of domino's pizza in Sukabumi. This research uses quantitative methods. The population in this study were Domino's pizza consumers in the city of Sukabumi and the sample used was 100 respondents. The data analysis technique used is simple linear regression analysis and the sampling technique used is probability sampling. The results of this study indicate that the differentiation strategy has a significant and positive influence on competitiveness. The results of the F test, namely the value of Fcount 374,749> 3.09 indicate that Fcount is greater than Ftable and the results of the correlation in this study have a very strong and high value of 0.890, so it can be concluded that the variable product quality influences competitiveness. Domino's pizza Sukabumi.